Algeria : 2006 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report ;, 2007)
Algeria's key challenges are to achieve sustained growth and reduce unemployment, while maintaining macroeconomic stability. This 2006 Article IV Consultation highlights that real GDP growth of Algeria temporarily declined to about 3 percent in 2006, largely because of a drop in hydrocarbon output for technical reasons. Inflation remained low through mid-year but is picking up. Monetary policy remained prudent, in line with the authorities' objective of containing inflation. The Bank of Algeria continued to absorb most of the excess liquidity of the banking system through deposit auctions in 2006.